Respuesta :

Answer:

[tex]-1 \le u, v \le 1[/tex] --- restriction

[tex]\sin(\cos^{-1}u + \sin^{-1}v) = \sqrt{(1 - u^2)(1 - v^2)} + uv[/tex]

Step-by-step explanation:

Given

[tex]\sin(\cos^{-1}u + \sin^{-1}v)[/tex]

Required

Write in terms of u and v

Let:

[tex]a =\cos^{-1}u[/tex]

Take arc cos of both sides

[tex]\cos a = u[/tex]

Using the following trigonometry identity

[tex]\sin^2a + \cos^2a = 1[/tex]

So:

[tex]\sin^2a = 1 -\cos^2a[/tex]

[tex]\sin^2a = 1 -u^2[/tex]

Take square roots of both sides

[tex]\sin a = \sqrt{1 -u^2[/tex]

So, we have:

[tex]\cos a = u[/tex]     [tex]\sin a = \sqrt{1 -u^2[/tex]

Let:

[tex]b =\cos^{-1}{\sqrt{1 - v^2}}[/tex]

Take arc cos of both sides

[tex]\cos b = \sqrt{1 - v^2[/tex]

So:

[tex]\sin^2b = 1 -\cos^2b[/tex]

[tex]\sin^2b = 1 - (\sqrt{1 - v^2})^2[/tex]

[tex]\sin^2b = 1 - (1 - v^2)[/tex]

[tex]\sin^2b = 1 - 1 + v^2[/tex]

[tex]\sin^2b = v^2[/tex]

Take square roots

[tex]\sin b = v[/tex]

So, we have:

[tex]\cos b = \sqrt{1 - v^2[/tex]     [tex]\sin b = v[/tex]

So, we have:

[tex]\sin(\cos^{-1}u + \sin^{-1}v)[/tex]

[tex]\sin(\cos^{-1}u + \sin^{-1}v) = \sin(a + b)[/tex]

Apply sine rule

[tex]\sin(\cos^{-1}u + \sin^{-1}v) = \sin a\ cos b + \sin b \cos a[/tex]

[tex]\sin(\cos^{-1}u + \sin^{-1}v) = \sqrt{1 - u^2} * \sqrt{1 - v^2} + v *u[/tex]

[tex]\sin(\cos^{-1}u + \sin^{-1}v) = \sqrt{(1 - u^2)*(1 - v^2)} + v *u[/tex]

Expand

[tex]\sin(\cos^{-1}u + \sin^{-1}v) = \sqrt{(1 - u^2)(1 - v^2)} + uv[/tex]

The restriction on u and v is:

[tex]-1 \le u, v \le 1[/tex]